1997
DOI: 10.1074/jbc.272.10.6226
|View full text |Cite
|
Sign up to set email alerts
|

A Protein-tyrosine Kinase-regulated, pH-dependent, Carrier-mediated Uptake System for Folate in Human Normal Colonic Epithelial Cell Line NCM460

Abstract: A significant proportion of the bacterially synthesized folate in the large intestine exists in the form of folate monoglutamate. Recent studies in our laboratory using human colonic apical membrane vesicles have shown the existence of an efficient carrier-mediated system for folate uptake. Nothing, however, is known about the cellular regulation of the colonic uptake process. In this study, we used a recently established human normal colonic epithelial cell line NCM460 to address this issue. Uptake of folic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 30 publications
4
47
0
Order By: Relevance
“…We focused on possible role of the cAMP/PKA-and the PTK-mediated pathways since these two pathways were reported to play a role in regulating folate uptake by other cells (11,17). The results showed that whereas modulators of cAMP/PKA-mediated pathway cause significant inhibition in folate uptake (and at both buffer pH 7.4 and 6.0), modulators of the PTK-mediated pathway failed to affect the uptake process.…”
Section: Discussionmentioning
confidence: 93%
“…We focused on possible role of the cAMP/PKA-and the PTK-mediated pathways since these two pathways were reported to play a role in regulating folate uptake by other cells (11,17). The results showed that whereas modulators of cAMP/PKA-mediated pathway cause significant inhibition in folate uptake (and at both buffer pH 7.4 and 6.0), modulators of the PTK-mediated pathway failed to affect the uptake process.…”
Section: Discussionmentioning
confidence: 93%
“…Folate receptors, anchored in the plasma membrane through a glycosylphosphatidylinositol moiety, translocate folates unidirectionally into cells via an endocytotic process (3)(4)(5)(6). A transport pathway with optimal activity at low pH has been described in murine leukemia L1210 cells (7,8), and a low pH route dominates transport of folates in intestinal cells (9,10).…”
mentioning
confidence: 99%
“…Possible regulation of thiamin uptake by pancreatic beta cells by intracellular regulatory pathways was also examined in this investigation with special focus on pathways that have been shown to regulate uptake of other nutrients and substrates in other cellular systems (i.e., PKA-, Ca 2ϩ /calmodulin-, and PTK-mediated pathways) (5,15,31). The results showed that although modulators of the PKA-mediated pathway failed to affect thiamin uptake, modulators (inhibitors) of the Ca 2ϩ / calmodulin-mediated pathway caused significant inhibition in the vitamin uptake process.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse-derived pancreatic beta-TC-6 insulinoma cells (passages [10][11][12][13][14][15][16][17][18][19][20][21][22] were obtained from American Type Tissue Collection (ATCC; Rockville, MD) and maintained in DMEM growth medium in the presence of 15 nM thiamin. Uptake was examined (unless otherwise stated) at 37°C in Krebs-Ringer buffer (in mM: 133 NaCl, 4.93 KCl, 1.23 MgSO 4, 0.85 CaCl2, 5 glucose, 5 glutamine, 10 HEPES, and 10 MES; pH 8.0) by a rapid filtration technique (14), as described by us previously (10,30).…”
Section: Culturing Of Pancreatic Beta-tc-6 Cells and Uptake Studiesmentioning
confidence: 99%